Climate Change Is Increasing the Risk of the Reemergence of Malaria in Romania. (26th October 2016) - Ivanescu, Larisa; Bodale, Ilie; Florescu, Simin-Aysel; Roman, Constantin; Acatrinei, Dumitru; Miron, Liviu
Abstract : The climatic modifications lead to global warming; favouring the risk of the appearance and development of diseases are considered until now tropical diseases. Another important factor is the workers' immigration, the economic crisis favouring the passive transmission of new species of culicidae from different areas. Malaria is the disease with the widest distribution in the globe. Millions of people are infected every year in Africa, India, South-East Asia, Middle East, and Central and South America, with more than 41% of the global population under the risk of infestation with malaria. The increase of the number of local cases reported in 2007–2011 indicates that the conditions can favour the high local transmission in the affected areas. In the situation presented, the establishment of the level of risk concerning the reemergence of malaria in Romania becomes a priority.